Macroepibiosis of three species of scallops in the waters of southern Primorye - Artem Yu. Baranov; Irina R. Levenets; Ludmila I. Sabitova; Evgeny B. Lebedev (Известия ТИНРО)
Composition and distribution of macroepibionts on scallops Swiftopecten swiftii, Mizuhopecten yessoensis and Azumapecten farreri (Pectinidae, Bivalvia, Mollusca) are investigated in 13 shallow-water areas at southern Primorye. The epibionts were collected from the upper and lower valves of living specimens of scallops in 1979-2016. The scallops (1150 specimens in total) were sampled by divers from natural and cultured dense populations of the mollusks. The depth and the type of bottom substrate were determined at each station. The sample size ranged from 10 to 72 individuals of scallops. All epibionts were removed from scallop shells, then fixed with 4 % formalin and preserved in 70 % alcohol, except algae; the algae were dried on air or frozen. The sampled macroepibionts were identified to species level and counted, except of amorphic encrusting organisms as hydroids, bryozoans and algae. Occurrence of boring polychaetes and sponges were determined by presence of the drilling traces. For common epibionts, the settlement density and biomass were determined for each scallop, mean values of these indices were calculated for entire sample, taking also into account the scallops without epibionts, then the biomass and density were recounted by a square decimetre. The epibionts were categorized into four groups, as the dominant, subdominant, typical, and others, with the biomass > 45 %, 15-30 %, 5-10 %, and < 5 %, respectively. The mean total biomass of epibiosis varied from 0.15 to 35.52 g/dm2, and the settlement density - from 1 до 220 ind./dm2. Mollusks, polychaetes and algae prevail in the most of areas both by the species number and occurrence. The highest biomass of crustaceans and polychaetes is recorded in suspended culture of M. yessoensis in the Ussuri Bay. High biomass of cirrepedes is recorded in natural populations of M. yessoensis and A. farreri at Vladivostok and in natural settlement of S. swiftii in the Vostok Bay. High biomass of polychaetes in epibiosis of M. yessoensis is recorded in the mixed settlement in the Posyet Bay and in natural polulation in the Nakhodka Bay. Mean total biomass and settlement density are generally higher in polluted and eutrophic areas where the most of epibionts (algae, cirripedes, serpulid polychaetes, oysters, bryozoans, ascidians) evidently suffer from siltation and prefer to attach to barnacle shells, dead or living, which are raised above the surface of scallop shells submerged into silt. Barnacles and serpulid polychetes dominate in these communities. In pure areas, as the southwestern Peter the Great Bay, the mean total biomass and settlement density of epibionts are lower. Macroalgae, bivalve and gastropod mollusks dominate by number and form the bulk of epibiosis biomass there. In on-bottom plantations of M. yessoensis where the scallops lie on the ground usually on the lower valve, the macroepibionts preferably colonize the upper valves of shells. In suspended plantations of this species, the total biomass of epibiosis is on average 10 times higher in comparison with on-bottom plantations; polychaetes, macroalgae (mostly Rhodophyta), crustaceans and ascidians are common epibionts there. In mixed settlements of M. yessoensis , the epibioses are the most diverse and abundant - the main taxa there are Polychaeta, Algae, Porifera and Mollusca; their total biomass is measured in grams per dm2. In natural scallop populations of M. yessoensis, the epibiotic communities are formed mainly on the upper valves of shells, but the epibioses have multilayer structure. Barnacles, polychaetes and bivalves are the basic epibionts for native M. yessoensis in polluted areas, but macroalgae, bivalves and gastropods - in pure areas. Infestation of scallop shells by boring polychaetes Polydora spp. and Dipolydora spp. increases with silting of bottom sediments from 27 to 100 %. Biomass of Cirripedia increases in epibiosis of native M. yessoensis to tens of grams per dm2. Composition of epibionts on scallops A. farreri and S. swiftii is investigated for the first time in 2 and 1 areas of southern Primorye, respectively. The epiobioses of A. farreri include 6 groups of animals (Porifera and Bryozoa as the basic ones) and S. swiftii - 4 groups (basically Bryozoa and Polychaeta). A. farreri and S. swiftii in their natural settlements often attach themselves to oyster or mussel druses and so they have different orientation in the near-bottom layer. Therefore, epibiotic communities could be formed both on the lower valves and upper valves of their shells. In opposite to M. yessoensis , cirripedes and polychetes never dominate in epibiotic community of A. farreri and S. swiftii . The epibiotic flora of three scallop species has 87 species, including 49 red algae, 16 brown algae, and 22 green algae. The red algae only (9 species) are recorded on the valves of S. swifti . 16 algal species are found on the valves of A. farreri : 13 red, 1 brown, and 2 green algae. Rhodophyta dominate in terms of species number in the epibiosis of M. yessoensis , except of its natural populations in the Nakhodka Bay where 50 % of algal species belong to Chlorophyta and in the Vostok Bay (41 %) and also suspended culture in the Ussuri Bay (41.5 % of Chlorophyta species). Brown algae have the maximum species number in the epibiosis of the natural scallop population at Vladivostok (28.5 %) and on-bottom culture in the Posyet Bay (27.0 %). Besides of the species and habitat differences, composition of epibioses depends on age of scallop and depth.